Correlation between biomarkers of exposure, effect and potential harm in the urine of electronic cigarette users - Jun Li; Monique Williams; Prue Talbot; Maciej Lukasz Goniewicz; Shane Sakamaki-Ching; My Hua; Steve M Bates; Andrew N Robinson; Timothy W Lyons (BMJ Open Respiratory Research, 2020)
Objectives To determine if urinary biomarkers of effect and potential harm are elevated in electronic cigarette users compared with non-smokers and if elevation correlates with increased concentrations of metals in urine.Study design and setting This was a cross-sectional study of biomarkers of exposure, effect and potential harm in urine from non-smokers (n=20), electronic cigarette users (n=20) and cigarette smokers (n=13). Participant’s screening and urine collection were performed at the Roswell Park Comprehensive Cancer Center, and biomarker analysis and metal analysis were performed at the University of California, Riverside.Results Metallothionein was significantly elevated in the electronic cigarette group (3761±3932 pg/mg) compared with the non-smokers (1129±1294 pg/mg, p=0.05). 8-OHdG (8-hydroxy-2′-deoxyguanosine) was significantly elevated in electronic cigarette users (442.8±300.7 ng/mg) versus non-smokers (221.6±157.8 ng/mg, p=0.01). 8-Isoprostane showed a significant increase in electronic cigarette users (750.8±433 pg/mg) versus non-smokers (411.2±287.4 pg/mg, p=0.03). Linear regression analysis in the electronic cigarette group showed a significant correlation between cotinine and total metal concentration; total metal concentration and metallothionein; cotinine and oxidative DNA damage; and total metal concentration and oxidative DNA damage. Zinc was significantly elevated in the electronic cigarette users (584.5±826.6 µg/g) compared with non-smokers (413.6±233.7 µg/g, p=0.03). Linear regression analysis showed a significant correlation between urinary zinc concentration and 8-OHdG in the electronic cigarette users.Conclusions This study is the first to investigate biomarkers of potential harm and effect in electronic cigarette users and to show a linkage to metal exposure. The biomarker levels in electronic cigarette users were similar to (and not lower than) cigarette smokers. In electronic cigarette users, there was a link to elevated total metal exposure and oxidative DNA damage. Specifically, our results demonstrate that zinc concentration was correlated to oxidative DNA damage.